2020
DOI: 10.3390/rs12081282
|View full text |Cite
|
Sign up to set email alerts
|

Inferring Surface Flow Velocities in Sediment-Laden Alaskan Rivers from Optical Image Sequences Acquired from a Helicopter

Abstract: The remote, inaccessible location of many rivers in Alaska creates a compelling need for remote sensing approaches to streamflow monitoring. Motivated by this objective, we evaluated the potential to infer flow velocities from optical image sequences acquired from a helicopter deployed above two large, sediment-laden rivers. Rather than artificial seeding, we used an ensemble correlation particle image velocimetry (PIV) algorithm to track the movement of boil vortices that upwell suspended sediment and produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(65 citation statements)
references
References 30 publications
1
62
0
Order By: Relevance
“…Therefore, interpolation and extrapolation may need to be undertaken. This may be achieved using the assumption that the Froude number varies linearly or is constant within a cross section (Le Coz et al, 2010) or based on theoretical flow field distributions (Leitão et al, 2018). Upon a complete profile, unit discharge can be calculated based on the specified water depth at a number of locations in the cross section, and this is then aggregated to provide the total river flow.…”
Section: Image-based Hydrometric Solutions: Existing Workflows and Limitationsmentioning
confidence: 99%
“…Therefore, interpolation and extrapolation may need to be undertaken. This may be achieved using the assumption that the Froude number varies linearly or is constant within a cross section (Le Coz et al, 2010) or based on theoretical flow field distributions (Leitão et al, 2018). Upon a complete profile, unit discharge can be calculated based on the specified water depth at a number of locations in the cross section, and this is then aggregated to provide the total river flow.…”
Section: Image-based Hydrometric Solutions: Existing Workflows and Limitationsmentioning
confidence: 99%
“…This approach to estimating water depth from averaged river images is synergistic with, and inspired by, parallel efforts to use image sequences to infer surface flow velocities via large-scale particle image velocimetry (LSPIV). For example, Legleiter and Kinzel (2020b) showed that continuous velocity fields could be derived from time series -3-…”
Section: Accepted Articlementioning
confidence: 99%
“…In addition to the videos, digital aerial photographs of the Salcha River also were acquired from the Robinson R44 on the same day. These images were captured by a Hasselblad A6D-100C 100 megapixel digital mapping camera deployed within a pod mounted on the helicopter's landing gear (Legleiter & Kinzel, 2020b). The data were collected while transiting a series of flight lines designed to provide complete coverage, with ample overlap, of the entire study area.…”
Section: Accepted Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, interpolation and extrapolation may need to be undertaken. This may be achieved using the assumption that the Froude number varies linearly or is constant within a cross section (Le Coz et al, 2010) or based on theoretical flow field distributions (Leitão et al, 2018). Upon a complete profile, unit discharge can be calculated based on the specified water depth at a number of locations in the cross section, and this is then aggregated to provide the total river flow.…”
Section: Image-based Hydrometric Solutions: Existing Workflows and LImentioning
confidence: 99%